The Effect of Volatility Changes on the Level of Stock Prices and Subsequent Expected Returns. - Haugen, Robert A; Talmor, Eli; Torous, Walter N (Journal of Finance, 1991)
This paper estimates volatility changes in daily returns to the Dow Jones Industrial Average over the sample period 1897 through 1988. This allow a direct investigation of the reaction of the level of stock prices and subsequent expected returns to these estimated changes in volatility. The authors provide empirical evidence consistent with relatively large and systematic revisions in stock prices and subsequent expected returns to volatility changes. However, there appears to be an asymmetry in the market's reaction to volatility increases as opposed to volatility decreases. A majority of their volatility changes cannot be associated with the release of significant economic information.